EDUKASI DAN MOTIVASI MENJADI INVESTOR DI PASAR MODAL SYARIAH (STUDI KASUS GALERI INVESTASI SYARIAH IAIN SULTAN AMAI - Ismail, Juniaty (Institut Agama Islam Negeri Parepare, 2020)
This research was conducted to determine the extent to which education is able to motivate young people to become investors in the Islamic capital market. Education is needed as a driving factor in a person to make decisions. IAIN Sultan Amai Gorontalo Islamic Investment Gallery is a forum used for potential investors and investors who are still operating until now. This study uses a descriptive qualitative approach, which is the method used to analyze data based on facts found in the field as evidence to answer what impact education has on investment motivation. Data collection techniques are interviews, and customer documentation of the Islamic Investment Gallery of Gorontalo State Islamic Institute. The results of the study revealed that with the education and motivation of GIS IAIN Sultan Amai Gorontalo, the number of customers was able to increase, in the March 2020 period the number of investors increased by 171, from 2019 which only reached 150 investors. And the factors that motivate students to invest in the Capital Market are because of the benefits, needs and long-term savings.